Acceptance and forgiveness therapy for veterans with moral injury: spiritual and psychological collaboration in group treatment. (14th April 2022) - Pernicano, Patricia U.; Wortmann, Jennifer; Haynes, Kerry
Abstract: The authors developed Acceptance and Forgiveness Therapy (AFT), a psychospiritual group intervention that guides veterans with moral injury experientially from a trauma-focused (damaged, broken, guilty, unforgivable, hopeless, unacceptable) to restorative (worthy, connected, hopeful, forgiven, responsible) view of self. A mental health (MH)-trained chaplain and MH provider, as co-leaders, provide psychoeducation, facilitate therapeutic interaction, and encourage home practice. The curriculum includes evidence-driven psychological interventions, spiritually oriented practices, and metaphor, story, and art to illustrate concepts and facilitate self-expression. Scores on the Brief Symptom Inventory-18 and Acceptance and Action Questionnaire-2 showed decreased distress and increased flexibility. Post-group drawings reflect renewed purpose, greater self-acceptance, and meaningful engagement with others. Retention rate across seven group administrations ranged from 50% to 100%. Outcomes suggest AFT is a promising practice for veteran moral injury meriting further study and implementation.